Artificial Intelligence Literacy Among Arabic Language Education Students: Influencing Factors and Pedagogical Implications - Astri Deliany Nurlestary; Muhammad Rifa'i; Arifah Nurtsania Ardiyanti; Oong Setiawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to determine the level of Artificial Intelligence (AI) literacy among Arabic Language Education (PBA) students ISQI Sunan Pandanaran, analyze the factors influencing this level, and explore its implications for Arabic language learning. This study uses a mixed method with a convergent design, combining quantitative data from questionnaires based on the Meta AI Literacy Scale (MAILS) and qualitative data from structured interviews. The results show that, in general PBA student’s AI literacy level is in the medium category. Students generally have an understanding and ability to use AI, but are still weak in aspects of technology creation and development. Supporting factors include ease of access, digital habits, and lecturer support, while inhibiting factors are limited infrastructure, the lack of integration of AI into the curriculum, and limited accuracy. The implications of AI literacy include benefits in searching for references and materials, personalized learning, translation, and strengthening language skills, but also potentially pose risks such as dependency, decreased basic language competency, inaccurate/miscontextualized information, and plagiarism. This study recommends integrating AI into the curriculum, training for lecturers and students, and providing adequate digital facilities.